The Effect of Correlation Between Prognostic Factors and Long-Term Mortality in Tongue Cancers - Gözde Orhan Kubat; Süha Beton; Muharrem Gerçeker (İstanbul Medical Journal, 2016)

(untitled)
Objective: The aim of this study was to review demographic data, prognostic factors, and the effect on mortality of patients who were treated for tongue cancer and followed up at our clinic.Methods: Data between 2000 and 2013 were retrospectively reviewed. This report includes data from 96 patients. Demographic data, dental prostheses, smoking and drinking habits, CVs, tumor characteristics, treatment methods, recurrence, distant metastasis, second primary tumor presence, postoperative survival, imaging techniques, and follow-up dates were reviewed.Results: According to the Kaplan–Meier survival analysis, the following results were observed: patients whose tumors were recurring and whose lymph nodes were positive in the neck and according to TNM staging; an increase in clinical and pathological T-N phase; and a decrease in survival time in 3, 5, and 10 years (p<0.05).Conclusion: Tumor stage, histopathological grade, growth pattern, lymph node and distant metastasis, and second primary tumor are important prognostic factors. The identification of tumors at an earlier stage has increased the survival time.